IMAGE OF THE MENTALLY ILL IN LITHUANIAN DAILY PRESS AND NEWS WEBSITES - Mataitytė-Diržienė, Jurga (Socialinė teorija, empirija, politika ir praktika, 2009)
According to the research Lithuanian society is intolerable to mentally ill people. Therefore the main aim of this research was to raise awareness and enhance knowledge about the media representations of mentally ill persons in Lithuania. The method used in this research was quantitative content analysis. 144 articles from national newspapers with some reference to mental illness appearing in the selected newspapers over a period of three months in the fall of 2008 were analyzed. The results of the research have shown that Lithuanian media creates quite negative images of mentally ill - most often it is a male, who has committed a crime, is very detailed identified in the article and whose opinion/version of the story is not important for the journalist. Mentally ill person is the source of information quite rarely. More often sources of information are the official persons. In most cases mentally ill person does not have a possibility to express his/hers opinion. There are just a few reportages in the analyzed data. This shows that journalists tend to distance themselves from mental health issues. They do not go out to the field to gather data, do not speak to the mentally ill people - it is safer for journalists to keep the distance by just giving references to events and not reporting about them. Very important actor in mental health area that is missing in the articles - is mental health institutions, even thou they dominate the mental health care system. Politics of mental health is not discussed at all in media in Lithuania.